Silence as Meaning: The Semiotics of Negative Space in Huang Binhong's Flower-and-Bird Paintings Introduction - Lei, Yun; Kookiattikoon, Supath (Journal of Posthumanism, 2025)
In Chinese ink painting, the unpainted surface is never truly empty. What may appear to Western eyes as mere negative space—the untouched paper surrounding a spray of plum blossoms or the void between a bird’s wings—functions in Huang Binhong’s (1865–1955) flower-and-bird paintings as a sophisticated visual language. This paper explores how Huang transformed the traditional practice of liubai (留白, “reserved blankness”) from a compositional device into a semiotic system—where absence speaks with as much force as form. While Huang’s revolutionary heimi (黑密, “black density”) style in landscape painting has received substantial scholarly attention, his strategic deployment of negative space in smaller-scale flower-and-bird compositions remains largely underexplored. Through close visual analysis and cultural semiotics, this study reveals how Huang’s voids operate as active signifiers—mediating between form and formlessness, text and image, tradition and modernity during the volatile years of Republican China.Huang’s blank spaces demand to be read, not merely seen. In Lone Plum Against Winter Sky (c. 1940s), for example, the stark emptiness encircling a gnarled branch does more than frame the subject—it becomes winter’s silence, the painter’s breath between strokes, and a visual analogue to the yin principle of Daoist cosmology. While classical liubai, particularly in Song dynasty painting, was used to suggest mist, water, or atmospheric perspective, Huang’s voids often refuse such representational logic. Instead, they become philosophical propositions—interrogations of perception itself.